Analisis Postur Kerja dalam Operasi Pemanenan Kayu: Pemuatan Log Secara Manual - Efi Yuliati Yovi; Lilis Eva Andriyani (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2019)
Lifting, pushing, and pulling activities combined with excessive material load and intense repetition have been reported to trigger excessive pressure on the lumbar disk (L5/S1). Using a static biomechanical approach (3DSSPP Version 7 software), this study presents empirical evidence proving that log loading activities with manual techniques are jobs that pose a high risk of injury to workers, indicated by (1) very high lifting index value (10), (2) compressive force that exceeds the maximum permissible limit of 6500 N, (3) difficult standing balance control, and (4) high potential of localized musculoskeletal fatigue in the workers. Musculoskeletal disorders analysis (using the Standardized Nordic Questionnaire instrument) shows intense disturbances in the lower back, shoulders, upper back, and hands. Interventions to reduce injury to the workers can be carried out by substituting work techniques (using aids devices), improving work administration (improving the standard operating procedure, supervision), and wearing anti-slip work shoes.